A Descriptive Study on the Infection Control Practices of Dentists in an Urbanized City in the Philippines During the COVID-19 Pandemic within the Period of General Community Quarantine (September 2020-MArch 2021)/Ma. Bianca B. Barrameda, Ma. Chrizel Ian A. Madlangbayan, and Joshua Marcel A. Sy. - Barrameda, Ma. Bianca B. Author
Introduction: The global impact of the COVID-19 pandemic has instigated a profound public health crisis, particularly affecting professionals like dentists who, due to their close interaction with saliva—a potential viral reservoir—and the aerosols generated during specific procedures, face elevated risks of infection. To mitigate this, the Centers for Disease Control and Prevention (CDC) and the Philippine Dental Association (PDA) have established guidelines deemed imperative for averting cross-infection in dental settings. This study, conducted in an urbanized Philippine city, delves into the infection control practices of dentists amid the pandemic.